The comparative effectiveness of Core versus Core+Enhanced implementation strategies in a randomized controlled trial to improve substance use treatment receipt among justice-involved youth - Danica K. Knight; Steven Belenko; Michael L. Dennis; Gail A. Wasserman; George W. Joe; Gregory A. Aarons; John P. Bartkowski; Jennifer E. Becan; Katherine S. Elkington; Aaron Hogue; Larkin S. McReynolds; Angela A. Robertson; et al. (BMC, 2022)
Abstract Background Most justice-involved youth are supervised in community settings, where assessment and linkage to substance use (SU) treatment services are inconsistent and fragmented. Only 1/3 of youth with an identified SU need receive a treatment referral and even fewer initiate services. Thus, improving identification and linkage to treatment requires coordination across juvenile justice (JJ) and behavioral health (BH) agencies. The current study examines the comparative effectiveness of two bundled implementation intervention strategies for improving SU treatment initiation, engagement, and continuing care among justice-involved youth supervised in community settings. Exploration, Preparation, Implementation, Sustainment (EPIS) served as the conceptual framework for study design and selection/timing of implementation intervention components, and the BH Services Cascade served as the conceptual and measurement framework for identifying and addressing gaps in service receipt. Methods Part of a larger Juvenile-Justice Translational Research on Interventions for Adolescents in the Legal System (JJ-TRIALS) Cooperative, this study involved a multisite, cluster-randomized control trial where sites were paired then randomly assigned to receive Core (training teams on the BH Services Cascade and data-driven decision making; supporting goal selection) or Core+Enhanced (external facilitation of implementation teams) intervention components. Youth service records were collected from 20 JJ community supervision agencies (in five states) across five study phases (baseline, pre-randomization, early experiment, late experiment, maintenance). Implementation teams comprised of JJ and BH staff collaboratively identified goals along the BH Cascade and used data-driven decision-making to implement change. Results Results suggest that Core intervention components were effective at increasing service receipt over time relative to baseline, but differences between Core and Core+Enhanced conditions were non-significant. Time to service initiation was shorter among Core+Enhanced sites, and deeper Cascade penetration occurred when external facilitation (of implementation teams) was provided. Wide variation existed in the degree and nature of change across service systems. Conclusions Findings demonstrate the criticality of early EPIS phases, demonstrating that strategies provided during the formative exploration and preparation phases produced some improvement in service receipt, whereas implementation-focused activities produced incremental improvement in moving youth farther along the Cascade.